Penerapan Hukum Pidana pada Kasus Cybercrime terkait Perlindungan Data Identitas - Haryono, Haryono; Sakti Myharto, Wiend (HUMANIORUM, 2026)
The development of information technology has brought both positive and negative impacts. One of the negative impacts that has emerged is the emergence of cybercrime, especially those involving the misuse of personal data or identity. Indonesia already has legal instruments in the form of Law Number 11 of 2008 concerning Electronic Information and Transactions (ITE Law) as amended by Law Number 19 of 2016, and Law Number 27 of 2022 concerning Personal Data Protection (PDP Law). However, the implementation and enforcement of the law still face challenges. Journal Article (Application of criminal law in cases of cybercrime and identity data), and reviewing one court decision as an example. but also throughout the world, and often carried out by the state, making cybercrime increasingly complex, the most common occurrence in Indonesia